Enhancing Restorative Justice in Indonesia: Exploring Diversion Implementation for Effective Juvenile Delinquency Settlement - Nashriana Nashriana; Desia Rakhma Banjarani; Marwin S Del Rosario; Vera Novianti (Faculty of Law, Sriwijaya University, Indonesia, 2023)
Indonesia’s juvenile delinquency is rapidly increasing in a high number every year. At the same time, restorative justice’s implementation through the diversion mechanism is ineffective. This circumstance indicates that efforts to enhance juvenile delinquency settlement are essential. Hence, this research elaborates on diversion challenges in settling cases involving juveniles in Indonesia. Moreover, it will analyse efforts to optimise diversion implementation in strengthening restorative justice in settling juvenile cases in Indonesia. This is normative research that uses a statutory approach and is described qualitatively. The research illustrates numerous obstacles in applying diversion during juvenile delinquency resolution in Indonesia. Amongst the difficulties are legal factors; law enforcer factors; factors of means or supporting facilities; societal factors, and cultural factors. These challenges incline the necessity to improve diversion applications in Indonesia’s juvenile delinquency. The effectiveness of diversion will contribute positively to the restorative justice system in Indonesia. Furthermore, optimising diversion is possible through reformulating regulation and prioritising prevention efforts to prevent juvenile delinquency from reaching litigation settlement.